2002
DOI: 10.1046/j.0016-8025.2001.00816.x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and stomatal control of photosynthetic enhancement in the canopy of a sweetgum (Liquidambar styraciflua L.) plantation during 3 years of CO2 enrichment

Abstract: Light-saturated photosynthetic and stomatal responses to elevated CO 2 were measured in upper and mid-canopy foliage of a sweetgum ( Liquidambar styraciflua L) plantation exposed to free-air CO 2 enrichment (FACE) for 3 years, to characterize environmental interactions with the sustained CO 2 effects in an intact deciduous forest stand. Responses were evaluated in relation to one another, and to seasonal patterns and natural environmental stresses, including high temperatures, vapour pressure deficits ( VPD ),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
114
2
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(130 citation statements)
references
References 48 publications
12
114
2
2
Order By: Relevance
“…It also improves nitrogen-use efficiency at both the leaf and canopy scale, while stimulating dark respiration via a transcriptional reprogramming of metabolism (Leakey et al, 2009). Experimental results indicate that plants are able to increase their water-use efficiency (WUE) as CO 2 levels rise (e.g., Picon et al, 1996;Morison, 1998), as has been corroborated under field conditions (Peñ uelas & Azcó n-Bieto, 1992;Ehrlinger & Cerling, 1995;Duquesnay et al, 1998;Gunderson et al, 2002;Ainsworth & Rogers, 2007). Studies have also identified interspecies variability in responses to increasing atmospheric CO 2 concentrations (e.g., Francey & Farquhar, 1982), and, importantly, have highlighted the possibility of species-specific response saturation rates (Waterhouse et al, 2004;Betson et al, 2007).…”
Section: Discussionsupporting
confidence: 52%
“…It also improves nitrogen-use efficiency at both the leaf and canopy scale, while stimulating dark respiration via a transcriptional reprogramming of metabolism (Leakey et al, 2009). Experimental results indicate that plants are able to increase their water-use efficiency (WUE) as CO 2 levels rise (e.g., Picon et al, 1996;Morison, 1998), as has been corroborated under field conditions (Peñ uelas & Azcó n-Bieto, 1992;Ehrlinger & Cerling, 1995;Duquesnay et al, 1998;Gunderson et al, 2002;Ainsworth & Rogers, 2007). Studies have also identified interspecies variability in responses to increasing atmospheric CO 2 concentrations (e.g., Francey & Farquhar, 1982), and, importantly, have highlighted the possibility of species-specific response saturation rates (Waterhouse et al, 2004;Betson et al, 2007).…”
Section: Discussionsupporting
confidence: 52%
“…In other words, the water use efficiency of plants is increased at high [CO 2 ]. Reductions in stomatal conductance induced by this physiological CO 2 effect are typically in the order of 10-40% (Morison, 1985;Field et al, 1995;Drake & Gonzàles-Meler, 1997;Medlyn et al, 2001;Gunderson et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Resultados semelhantes foram encontrados para Liquidambar styraciflua cultivadas em FACE sob elevado CO 2 , onde a redução na condutância é menor em relação ao tratamento ambiente (Gunderson et al, 2002;Wullschleger et al, 2002;Herrick et al, 2004). Em experimentos com plantas cultivadas sob elevado CO 2 , em períodos de seca, foi observado que a resposta ao CO 2 é maior devido à baixa condutância das plantas desse tratamento (Gunderson et al, 2002;Leakey et al, 2004Leakey et al, , 2006.…”
Section: O Efeito Da Concentração Do Co 2 Na Fotossíntese Realizada Eunclassified